A case of recurrent gallstone ileus: the fate of the residual gallstone remains unknown. (19th April 2014) - Aslam, Jamil; Patel, Prashant; Odogwu, Steve
Abstract : Gallstone ileus is a serious complication of cholelithiasis where mechanical small bowel obstruction occurs. The recurrence of gallstone ileus is rare. The 67-year-old woman in this case report had three known gallstones transit her small bowel with two causing obstruction and the third causing a 'tumbling phenomenon'. As we have an ageing population, and gallstone ileus has a higher incidence in the over 65 age group, associated with increased comorbidities and hence greater mortality rates, it is imperative to establish the best surgical intervention for it. This case report highlights the difference CT of the abdomen has made to the diagnosis of gallstone ileus and the pros and cons of the surgical management options.